Conception rate and foetal sex determination in crossbred cattle artificially inseminated with sex-sorted frozen bull semen under field conditions: a comparative study - Rajalakshmi, R; Rangasamy, S; Krishnakumar, K; Thilak Pon Jawahar, K (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was performed to test the fertility of commercially procured sex-sorted frozen bull semen straws in crossbred cattle of Thiruvallur district of Tamil Nadu under field conditions. A total of 60 crossbred heifers and 60 crossbred cows were inseminated with sex-sorted semen straws containing 2 x 106 X-bearing, frozen spermatozoa from six different bulls. Early pregnancy diagnosis was performed around 28-30 day post insemination using commercially available kits. The pregnancy rates were 31.67 per cent (19/60) and 30.00 per cent (18/60) in heifers and cows, respectively and were 40.9 (9/22), 30.77 (4/13), 27.27 (3/14) and 18.18 (2/11) between cows in first, second, third and fourth calving, respectively. The mean pregnancy rates between animals inseminated with Jersey crossbred and Red Sindhi sex-sorted frozen bull semen were 30.00±5.0 and 31.25±6.9, respectively. The conception rate was not statistically significant (P>0.05) between the groups. Foetal sex determination at 65-80 days post insemination using ultrasonography confirmed female foetus in all the pregnancies. Hence, the present field trial concludes similar pregnancy rates with the commercially procured X-bearing sex-sorted frozen semen straws in crossbred cattle along with foetal sex determination revealing female foetus in all pregnant animals.